Analytical control of lactide synthesis - Krutas D. S. Darjya Sergeevna; Zamanova M. K. Margarita Karimovna; Lukjyanov A. E. Aleksandr Evgenjevich; Zinovyev (Zinovjev, Zinoviev) A. L. Alexey Leonidovich; Novikov V. T. Viktor Timofeevich; Volgina T. N. Tatiana Nikolaevna (2016, 2016)
Title screen